Resistance of surfaces treated with 2K polyurethane and 2K acryl-izocyanate coatings to dry heat - Temelkova, Anastasija; Jaic, Milan (FDTME-Skopje, 2013)
This paper studies the resistance of treated surfaces to the action of dry heat, by observing the changes of the surfaces for a predefined temperature. The surfaces of solid wood samples were treated with two types of coatings: 2K polyurethane and 2K acryl-izocyanate coating. The aim of this study was to determine which of the coatings applied will give a better resistance to dry heat for given temperatures. The test results indicate that the dry heat causes damage with different intensity to the treated surfaces. The surfaces treated with 2K acryl-izocyanate coating show higher resistance than the surfaces treated with 2K polyurethane coating, i.e. the latter areless resistant to the action of dry heat. By applying modified polyurethane coatings, better resistance of surfaces to dry heat is achieved
Keywords: treated surface, coatings, 2K polyurethane, 2K acryl-izocyanate